SARS-CoV-2: comparison of IgG levels at 9 months post second dose of vaccination in COVID-survivor and COVID-naïve healthcare workers - Shah, Shagun B.; Chawla, Rajiv; Rawal, Sudhir K.; Mehta, Anurag; Parkash, Anuj (International Journal of Research in Medical Sciences, 2022)
Background: Natural (asymptomatic/symptomatic COVID-19 infection) and artificial (vaccination) exposure to the pathogen represent two modes of acquiring active immunity. No definitive guidelines exist regarding whether COVID-survivors (with infection/re-infection/re-re-infection in the three COVID-19 waves) require a modified vaccination schedule. Most countries are offering a third vaccine dose and many are contemplating a fourth dose. Our aim was to gauge the IgG-antibody levels 9m post second vaccination in healthcare workers (HCW) and compare these with IgG-levels 1m post-vaccination in the same cohort for any decline, and to compare the post-vaccination IgG-levels in COVID-survivors and COVID-naïve HCW at 9m. Methods: This prospective observational single-centric cohort study included 63 HCW of either sex, aged 18-70y who completed 9m post-vaccination. The IgG-titre was tested at 9-10m post second vaccination in COVID-survivors and COVID-naïve HCW. Results: At 1m and 9m post-vaccination IgG-levels in COVID-survivors (23.097±4.58 and 15.103±4.367 respectively; p<0.0001) and COVID-naïve HCW (16.277±6.36 and 9.793±6.928 respectively; p=0.0013) had unequal variance (Welsch test; p=0.0022 at 9m). 9/31 COVID-naïve HCW but none of the 32 COVID-survivors tested COVID-positive in the second wave post second vaccination. 11/31 and 3/32 HCW belonging to the former and latter groups developed COVID-19 in the third wave consequently deferring their third/precautionary vaccination. Conclusions: Although HCW with IgG-levels in all brackets developed COVID-19, the severity of symptoms corresponded with the IgG-levels. COVID-19 is here to stay, but in peaceful co-existence in endemic proportions. Considering evidence that immunity acquired by vaccination/natural infection is ephemeral, re-invention of vaccines to match the ever-mutating virus is foreseen.